Is Financial Literacy Associated With SME Sustainability During COVID-19? - Zaitul, Zaitul; Ilona, Desi (KnE Social Sciences, 2022)
The role of small-medium enterprises (SMEs) and their contributions to the economy are well recognized in the literature. However, SMEs have been challenged by COVID-19. There are limited empirical findings suggesting how the government lockdown policy affected SME sustainability. This study investigated the sustainability of Indonesia’s SMEs, and their social media adoption, financial literacy and financial access during the COVID-19 pandemic. This study also determined the effect of social media adoption, financial literacy, and financial access on SME sustainability. The resources-based theory was applied to understand the phenomena. Twenty-six SMEs operating in Pariaman city participated in this study. Variables were measured by a five- point Likert scale, and were analyzed descriptively. Furthermore, structural equation modelling was utilized, and in this case, smart-pls 3.2.8. was used. The results showed that the level of social media adoption was extremely low (mean = 2.20). The SMEs’ financial literacy was adequate (mean = 3.56). SMEs could access financial resources (mean = 3.84). Finally, the sustainability of SMEs was extremely low (mean = 2.35). Also, out of the three latent independent variables (social media adoption, financial literacy, financial access), only social media adoption had a positively significant effect on SME sustainability. This study implies that SMEs should increase social media adoption to gain higher sustainability. The authority should help build SME capabilities in digital marketing so that they survive in this turbulent time. This study contributes to the resources-based theory because variation in SME sustainability was determined by the SMEs’ resources, such as their digital marketing capability. Keywords: SME sustainability, financial literacy, financial access, social media adoption